Therapeutic Effect of Siegesbeckia pubescens on Cartilage Protection in a Rabbit Collagenase-Induced Model of Osteoarthritis - Jeong-Eun Huh; Yong-Hyeon Baek; Jae-Dong Lee; Do-Young Choi; Dong-Suk Park (Elsevier, 2008)
Siegesbeckia pubescens (S. pubescens) was widely used to alleviate symptoms of osteoarthritis (OA) in traditional medicine. However, the mechanism of action of S. pubescens remains unresolved. In the present study, we determined the physiological relevance of S. pubescens on cartilage protection in collagenase-induced osteoarthritis (CIA) in rabbits. The right knees of rabbits were injected intra-articularly with collagenase, and rabbits were orally administered with distilled water (vehicle), S. pubescens (100, 400 mg/kg) or celecoxib (100 mg/kg) once a day for 28 days after the initiation of the CIA. S. pubescens significantly suppressed the stiffness and global histological score including articular cartilage and synovial layer in CIA. Proteoglycan, aggrecan, and type II collagen expression was significantly increased in the rabbit knee joints of the S. pubescens-treated group. However, celecoxib had no effect on cartilage protection in CIA. The expression level of ADAMTS-4, ADAMTS-5, MMP-1, MMP-3, and MMP-13 were dose-dependently decreased in the S. pubescens-treated group. In contrast, the level of TIMP-1 dose-dependently increased. The pro-inflammatory cytokines involved in cartilage destruction, such as IL-1β, and inflammatory mediators containing PGE2 and NO were also inhibited in the S. pubescens-treated group. These results indicate that the cartilage protective effect of S. pubescens works through down-regulation of inflammatory mediators and aggrecanases and MMPs, while up-regulating TIMP-1 in the CIA rabbit model. Keywords:: Siegesbeckia pubescens, osteoarthritis, cartilage protection